Hierarchical influences of prey distribution on patterns of prey capture by a marine predator. (2nd May 2017) - Carroll, Gemma; Cox, Martin; Harcourt, Robert; Pitcher, Benjamin J.; Slip, David; Jonsen, Ian
Summary: Prey distribution acts at multiple spatial scales to influence foraging success by predators. The overall distribution of prey may shape foraging ranges, the distance between patches may influence the ability of predators to detect and move between profitable areas, and individual patch characteristics may affect prey capture efficiency. In this study, we assessed relationships between spatially explicit patterns of prey capture by a central place forager, the little penguin (using GPS tracking and accelerometry), and the distribution of aggregations of potential forage fish prey (using boat‐based active acoustics) in eastern Australia. We used complementary resource selection functions to estimate the distribution of both prey captures and aggregations across the study area, based on a suite of habitat characteristics. We found that 99% of prey captures by penguins occurred in the top 20 m of the water column. The estimated distribution of prey captures across the study area was similar to the distribution of aggregations above 20 m depth, indicating that penguins effectively matched the local distribution of their prey. The distances between consecutive prey captures followed a bimodal distribution, with means of 8·1 ± 2·2 and 57·4 ± 1·7 m. Based on the length of aggregations and the distances separating aggregations along survey transects, this implies that foraging behaviour occurs on multiple spatial scales corresponding to within‐patch and between‐patch movements respectively. Morphological characteristics of aggregations above 20 m depth were important for explaining variance in the number of prey caught by penguins in an area, with penguins catching more prey where aggregations were relatively dense, compact and shallow. These results reveal spatially explicit patterns of prey capture, and provide a framework for understanding how features of prey distribution influence prey intake by predators in patchy environments. A lay summary is available for this article. Abstract : Lay Summary